Phytochemical Constituents and Biological Activities of Jasonia glutinosa L.: The First Report for the Plant Growing in North Africa - Hamdoon A. Mohammed; Abdulnaser Kh. Abdulkarim; Abdullah D. Alamami; Fatma A. Elshibani (Journal of Chemistry)
Jasonia glutinosa (rock tea), also known as Chiliadenus glutinosa Cass., is a medicinal plant growing in the Mediterranean Basin. It is used for the treatment of depression, gastrointestinal complaints, inflammations, appendicitis, colds, and respiratory disorders. The current study is the first report for the plant species growing in Libya and aims to investigate the phytochemical constituents, antioxidant, cytotoxic, and antimicrobial activities of the plant’s aqueous ethanolic extract. The phytochemical investigation was conducted by the spectrophotometric quantitative assay and the LC-MS analysis. The analysis revealed the presence of 14.67 and 46.72 mg/g of the total phenolics and flavonoids equivalent to gallic acid and rutin, respectively. A total of thirty compounds of phenolic acids and flavonoids were identified by the LC-MS analysis, with a total relative percentage of 18.69%. The analysis revealed the dominance of methoxylated flavonoids and cinnamic acid derivatives, including caffeoylquinic acids. The in vitro antioxidant assays showed 265.55, 513.32, and 27.10 μM Trolox eq/mg of extract in the ABTS, ORAC, and FRAP assays, respectively. Cancer cell growth inhibitions of 9.23, 11.42, and 34.01% at a concentration of 100 μg/mL against MCF-7, HepG2, and PANC-1 cell lines were obtained, which is considered a weak cytotoxic effect when compared to the standard anticancer agent, doxorubicin (DOX). No antimicrobial activity was noticed for the plant extract against all tested microorganisms, i.e., Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Salmonella typhimurium, Candida albicans, and Saccharomyces cerevisiae. The weak antimicrobial effect of the plant did not support the claim of traditional use of the plant as an antimicrobial agent.